PROOXIDANT-ANTIOXIDANT HOMEOSTASIS IN THE TISSUES OF THE UTERUS OF PIG, DEPENDING ON THE PERIODS OF THE REPRODUCTIVE CYCLE - Кузьменко, Л.М.; Поліщук, А.А.; Усенко, С.О.; Шостя, А.М.; Стояновський, В.Г.; Карповський, В.І.; Білаш, С.М. (World of Medicine and Biology, 2018)
The article highlights studying results of disclosure of the peculiarities of formation prooxidant-antioxidant homeostasis in the tissues of the uterus of pig in the different periods of the reproductive cycle and pregnancy. In experiments on the basis of analogies were used 40 clinically healthy pigs of large white breed aged 8 months and weighing 125-130 kg. The pigs were kept in fences, 10-11 animals in each group. Not inseminated and pregnant sows were fed according to the rules taking into account their physiological state. The pigs and pig sows were slaughtered at different periods of the reproductive cycle: luteal phase (10 days after ascertainment of the immobility reflex, estrus (24 hours after the beginning of the estrus), 10, 15, 20, 30, 60 and 90 days of pregnancy. After slaughter, samples of tissues were taken from the sows: the mucous membrane and muscle of the uterus to determine components of prooxidant-antioxidant homeostasis in them. It has been established that the state the prooxidant-antioxidant homeostasis in tissues of the horns of the pig uterus of are labile and depends on the period of reproductive cycle. It was revealed that in the endometrium and myometrium with the beginning of the period of the estrus – the growth of activity catalase (р